Risky drug use and effects on sleep quality and daytime sleepiness. (25th May 2015) - Ogeil, Rowan P.; Phillips, James G.; Rajaratnam, Shantha M. W.; Broadbear, Jillian H.
<x xml:space="preserve">Abstract</x> Objective Sleep problems are commonly reported following alcohol and cannabis abuse, but our understanding of sleep in non‐clinical drug using populations is limited. The present study examined the sleep characteristics of alcohol and cannabis users recruited from the wider community. Methods Two hundred forty‐eight self‐identified alcohol and/or cannabis users (131 women and 117 men) with a mean age of 26.41 years completed an online study that was advertised via online forums, print media and flyers. As part of the study, participants completed validated sleep scales assessing sleep quality (Pittsburgh Sleep Quality Index) and excessive daytime sleepiness (Epworth Sleepiness Scale) in addition to validated drug scales assessing alcohol (Alcohol Use Disorders Identification Test) and cannabis (Marijuana Screening Inventory) use. Results Problems with sleep quality were more commonly reported than were complaints of excessive daytime sleepiness. Clinically significant poor sleep quality was associated with comorbid problem alcohol and cannabis use. Women reporting problem alcohol and cannabis use had poorer sleep outcomes than men. Conclusions Social drug users who report risky alcohol and cannabis use also report poor sleep. Poor sleep quality likely exacerbates any drug‐associated problems in non‐clinical populations. Copyright © 2015 John Wiley & Sons, Ltd.